Methodology for the inclusion of environmental criteria in public procurement: Case study Tecnológico de Costa Rica - Salazar-Rojas, Teresa (2021)
The public sector is the main consumer of the country; therefore, it has the capacity to drive markets towards sustainable production models. Costa Rica has initiatives to promote green and sustainable public procurement. However, there is still lack of knowledge and lack of experience. This research proposes a methodology applicable to any public entity for the inclusion of environmental criteria in its procurement processes and was developed at Tecnológico de Costa Rica (TEC). To this end, four product categories were prioritized, environmental criteria were determined with their respective evidences of verification and market consultations were carried out to determine the feasibility of compliance. Finally, the criteria were classified according to the current legislation. The selected product groups, considering the annual expenditure of the institution–budget, purchasing volume, internal use coverage and environmental impact, were furniture, office supplies, clothing and food services; resulted in a higher compliance rate of specifications for the suppliers of the first two categories. In the case of textiles was found deficiencies about the environmental traceability of raw materials and production processes, for the latter category shows the lack of training of the companies and the insufficient progress of eco-labeling programs in meat products at national level.